The Role of Racial and Ethnic Factors in MicroRNA Expression and Risk for Type 2 Diabetes - Flowers, Elena; Kanaya, Alka M.; Zhang, Li; Aouizerat, Bradley E. (Frontiers in Genetics, 2022)
Prior studies focused on circulating microRNAs and the risk for complex diseases have shown inconsistent findings. The majority of studies focused on European and East Asian racial or ethnic groups, however, ancestry was not typically reported. We evaluated the risk for type 2 diabetes as an exemplar to show that race and ethnic group may contribute to inconsistent validation of previous findings of associations with microRNAs.